PENDUGAAN HERITABILITAS DARI 15 GENOTIPE PEPAYA (Carica papaya L.) PADA DUA PERIODE MUSIM PANEN - TRI BUDIYANTI; SUNYOTO SUNYOTO (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
The objectives of this research were to estimates the genetic diversity and heritability of production characters and fruits quality of papaya on two harvest periods. This experiment was conducted at three locations e.i Bogor, West Java from Januari 2012 to March 2013. The treatments were arranged in randomized complete block design (RCBD), consisting of 15 genotypes as treatment with three replications at two harvest periods. Data observed were analysed by analysis of variance and mean square of each character was used to estimate the number of genetic diversity and broad sense heritability (h2bs). Character such fruit weigth, fruit length, flesh hardness flesh thickness, fruit number, production per plant had high heritability.